MENINGKATKAN KETERAMPILAN PROSES DAN PENGUASAAN PENGETAHUAN SISWA KELAS XI IPA MELALUI METODE IMPROVE - Widyastuti Ismani; Nila Kartika Sari (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study is to improve the process skills and mastery of students' knowledge in linear program material through the improve method in class XI IPA 4 SMA Negeri 1 Pandaan. This research is a classroom action research (CAR) with the Kemmis and McTaggart models, through two stages: (1) the initial observation stage (pre-action); and (2) the implementation phase of the action. Data instruments used were (1) an observation sheet to assess students 'learning process skills, and (2) written test questions sheets in the form of a post test to conduct an assessment of the mastery of students' learning outcomes. The data analysis technique used is the triangulation technique. The results showed there was a significant increase in the learning process skills and the mastery of students' learning outcomes knowledge. Based on the results of these achievements, it is necessary to take alternative actions in implementing appropriate and effective improve methods.